Revisiting South African History: Multiple Perspectives in the Novels of Nadine Gordimer - Rosalía Baena Molina (Miscelánea: A Journal of English and American Studies)
Narrative perspective is a particularly relevant prism through which the relations between literature and history can be viewed. Nadine Gordimer’s novels have often been analyzed as historical artifacts that give insight on South African historical situations, and the players in the drama. This paper suggests that a narratological study of point of view and the examination of diverse perspectives in the different novels sheds light on an understanding of the conflicts enacted in her fiction. The flexibility in her manipulation of point of view is observed in particular in four novels: A Guest of Honour (1971), The Conservationist (1974), Burger’s Daughter (1979), and My Son’s Story (1991). Her novels thus pose in acute form the question of whose story will be told and who will tell it. The multiplicity of voices and the corresponding shifts in focalization evident in her novels provide ways to explore the nature of both the creative act and the connection between the personal and the political.